Physical itness, diet and digital leisure depending on physical activity in university students from Granada - Chacón-Cuberos, R.; Zurita-Ortega, F.; Ubago-Jiménez, J. L.; González-Valero, G.; Sánchez-Zafra, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The present study aims to analyze the body composition, VO2max, flexibility, diet and problematic use of video games according to sex and the practice of physical-sport activity in a sample of university students from the province of Granada. A total of 138 subjects participated in this descriptive and cross-sectional study with a mean age of 22.60 ± 2.79 years and a gender distribution of 65.9% (n = 91) for men and 34.1% (n = 47) for women. The main results showed that males had a higher VO2max and lean mass, in addition to showing a higher problematic use of video games. Moreover, university students who practice physical activity more than three hours a week had a higher lean mass and VO2max. Similarly, the problematic use of video games is higher in young people who are physically active because of their techno-active profile.